Green Accounting as a Learning Tool: Strengthening Environmental Literacy in Senior High School Economics Education - Amri Dhimas Maulana; Umi Sakinah; Iseu Anggraeni; Nabella Dananier; Asnan Purba (Tazkia Islamic University College, 2025)
This research tries to explore how Green Accounting can be used as a learning tool to strengthen environmental literacy in high school Economics lessons. This research uses a qualitative approach with a case study design. The research was conducted in a senior high school (SMA Negeri 2 Tanggul, Jember Regency) that has started to integrate environmental issues into the teaching-learning process. Data were collected through interviews with teachers, direct observation in the classroom, and analysis of learning documents such as lesson plans and student assignments. The results showed that when students learn accounting not only from the financial side, but also consider the social and environmental impacts of economic activities, they become more concerned and critical of sustainability issues. Teachers utilize project-based and contextual learning approaches so that students can relate theory to real problems around them, such as environmental pollution or waste management. This process helps students see that accounting is not just about numbers, but can also be a way to take care of the earth. This finding shows that economic education that promotes sustainability is not only possible in schools, but also very important to form a young generation that cares and is responsible for the future of their environment.